2017
DOI: 10.1158/2159-8290.cd-16-1297
|View full text |Cite
|
Sign up to set email alerts
|

PAX3–FOXO1 Establishes Myogenic Super Enhancers and Confers BET Bromodomain Vulnerability

Abstract: Alveolar rhabdomyosarcoma is a life-threatening myogenic cancer of children and adolescent young adults, driven primarily by the chimeric transcription factor PAX3-FOXO1. The mechanisms by which PAX3-FOXO1 dysregulates chromatin are unknown. We fi nd PAX3-FOXO1 reprograms the cis -regulatory landscape by inducing de novo super enhancers. PAX3-FOXO1 uses super enhancers to set up autoregulatory loops in collaboration with the master transcription factors MYOG, MYOD, and MYCN. This myogenic super enhancer circui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
370
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(404 citation statements)
references
References 59 publications
19
370
0
Order By: Relevance
“…As super enhancers have been shown to regulate cell identity and oncogenes Lovén et al, 2013), our findings suggest that these FLC-specific enhancer hotspots may regulate genes important in the formation, progression, and/or maintenance of this cancer. Super enhancers are regulated by the bromodomain protein BRD4 (Lovén et al, 2013), and BRD4 inhibitors such as JQ1 (Filippakopoulos et al, 2010) have been shown to disrupt super enhancer function (Gryder et al, 2017;Lovén et al, 2013;Mack et al, 2018;Peeters et al, 2015). Pharmacological disruption of the FLC-specific enhancer hotspots we have described here may represent an alternative therapeutic approach for FLC.…”
Section: Discussionmentioning
confidence: 80%
“…As super enhancers have been shown to regulate cell identity and oncogenes Lovén et al, 2013), our findings suggest that these FLC-specific enhancer hotspots may regulate genes important in the formation, progression, and/or maintenance of this cancer. Super enhancers are regulated by the bromodomain protein BRD4 (Lovén et al, 2013), and BRD4 inhibitors such as JQ1 (Filippakopoulos et al, 2010) have been shown to disrupt super enhancer function (Gryder et al, 2017;Lovén et al, 2013;Mack et al, 2018;Peeters et al, 2015). Pharmacological disruption of the FLC-specific enhancer hotspots we have described here may represent an alternative therapeutic approach for FLC.…”
Section: Discussionmentioning
confidence: 80%
“…It is proposed that the PAX‐FOXO1 proteins mediate their transcriptional impact by recruiting other transcription factors and chromatin‐binding proteins, such as BRD4, to form super‐enhancers. Moreover, transcription may be driven by three‐dimensional looping that brings PAX‐FOXO1‐associated super‐enhancers to promoters and enables physical interaction of super‐enhancer‐bound proteins with promoters . As the lack of DNA methylation is fundamental to open chromatin states, we hypothesize that promoter DNA hypomethylation may coordinate with PAX‐FOXO1 to drive target gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transcription may be driven by three-dimensional looping that brings PAX-FOXO1-associated super-enhancers to promoters and enables physical interaction of super-enhancer-bound proteins with promoters. 40 As the lack of DNA methylation is fundamental to open chromatin states, we hypothesize that promoter DNA hypomethylation may coordinate with PAX-FOXO1 to drive target gene expression. In accord with this concept, we observed a significant depletion of DNA methylation in the promoter region in FP compared to FN RMS tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic processes such as histone modifications at cis-regulatory elements can affect gene transcription independent of their orientation or distance via enhancers 25 . H3K27ac has been established as an important mark of enhancers which distinguishes between active and inactive regions (active referring to a positive influence on the expression of proximal genes) 26 , hence, regions with deposits of H3K27ac are often associated with enhanced gene activity 26,27 . We performed Chromatin Immunoprecipitation (ChIP) experiments for H3K27ac in the presence of DMSO, ipatasertib, enzalutamide or the combination of both ipatasertib and enzalutamide, with RNA-seq performed in parallel.…”
Section: Inhibition Of Akt Blocks the Induction Of Gr Expression And mentioning
confidence: 99%